The Role of the Aboge Calendar in the Community of NU Besuk Village, Probolinggo Regency - Muhamad Ja'far Sodiq (Lakpesdam PCNU Kota Salatiga, 2022)
The Aboge Islamic Community is the result of acculturation of Islamic culture with Java and is able to become a community with a new face that distinguishes them from other Islamic communities and has a characteristic that is the calendar that is applied. The Aboge calendar has become the culture of the NU community of Besuk village. This research was conducted in Besuk Village, Bantaran District, Probolinggo Regency. The object of this research is the Aboge Islamic calendar, while the material object is the NU community of Besuk village. This study aims to reveal the role of the Aboge Islamic calendar in the NU community of Besuk village and the history of the Aboge Islamic community in Besuk village. the method used is the ethnographic method. The results of the study concluded that: Islam Aboge in Besuk village was brought by Kiai Tahmid which was then continued by his children and grandchildren. The Aboge calendar is the result of acculturation of Javanese culture with Islam, in its calendar consisting of eight years, twelve months and seven days. The NU community of Besuk village still maintains the Aboge calendar as their culture. The accuracy of the calculations in the Aboge calendar is the main reason the NU community of Besuk village maintains the Aboge calendar. The accuracy of the calculations in the Aboge calendar is the main reason the NU community of Besuk village maintains the Aboge calendar and becomes the culture of the NU community of Besuk village. The role of the Aboge calendar is carried out when holding weddings, determining residence, building houses and others.